Identification of Novel Pathogenic Variants in Tunisian Patients with Developmental and Epileptic Encephalopathy Using Targeted High Throughput Sequencing - Said, Mariem Ben; Jallouli, Olfa; Aissa, Abir Ben; Souissi, Amal; Kamoun, Fatma; Fakhfakh, Faiza; Masmoudi, Saber; Ayed, Ikhlas Ben; Triki, Chahnez Charfi (Medical Science: Recent Advances and Applications Vol. 1, 2025)
Background: In Tunisia, Developmental and epileptic encephalopathy (DEE) imposes a significant burden on the family and the healthcare system. However, data regarding the genetic basis of epilepsy in the country remains scarce. Objective: The aim of this study was to develop a high-throughput sequencing panel for diagnosing developmental and epileptic encephalopathy in Tunisia and to determine the prevalence of disease-associated genes in this region. Methods: A custom next-generation sequencing panel was created to analyze the coding sequences of 116 genes in individuals with developmental and epileptic encephalopathy from the Tunisian population. Segregation analysis and in silico assessments were performed to evaluate the pathogenicity of the identified variants. Results: 12 pathogenic variants in the genes SCN1A, CHD2, CDKL5, SZT2, KCNT1, GNAO1, PCDH19, MECP2, GRIN2A, and SYNGAP1 in patients with developmental and epileptic encephalopathy were identified. Five of these variants are novel. Moreover, genetic results influenced treatment decisions for four of the patients. Significance: This study represents the first report of a custom genetic panel for detecting variants associated with developmental and epileptic encephalopathy in the Tunisian population and the North African region (Tunisia, Egypt, Libya, Algeria, Morocco), achieving a diagnostic rate of 30%. The high-throughput sequencing panel significantly improved the positive diagnostic rate for developmental and epileptic encephalopathy in Tunisia, where the rate was previously less than 15% using Sanger sequencing. Both physicians and parents recognized the value of genetic testing in these cases.